From ashes to action cross-border sharing session from New Zealand - Xin Wee, Chen (Faculty of Medicine, 2023)
The Department of Public Health Medicine is honored to invite Prof Chris Bullen, a professor from the School of Public Health, The University of Auckland Waipapa Taumata Rau, New Zealand. He is also the Society for Research on Nicotine & Tobacco president and the director of the National Institute for Health Innovation, University of Auckland, New Zealand. The webinar entitled "From Ashes to Action" aims to share effective tobacco control strategies from a public health perspective.